Analisis Etika Profesi Akuntan dalam Standar Internasional - Fitriyanti, Rani; Dewi Suprihandari, Miya (CV. Lafadz Jaya, 2022)
This study discusses the ethical analysis of the accounting profession in international standards. Accountants are one of the important professions in the business world because they are related to finance, therefore it is obligatory for an accountant to apply the ethics of the existing accounting profession. The purpose of this study was to find out the violations of the accounting profession's ethics that occurred. Professional ethics are intended as guidelines and rules for all members, whether practicing as auditors, private workers, workers in government agencies, or in the world of education. The method used is a type of library research, namely research is carried out only from written works, both research results that have been published and those that have not. This study uses qualitative data collection using existing data, such as using data reduction and then drawing conclusions using logic, aesthetics, and ethics. This research was made by examining the acquisition of secondary data sourced from other parties.